Using administrative records to support the linkage of census data: protocol for building a longitudinal infrastructure of U.S. census records - Alexander, Joseph; Genadek, Katie (International Journal of Population Data Science, 2023)
This article describes the linkage methods that will be used in the Decennial Census Digitization and Linkage project (DCDL), which is completing the final four decades of a longitudinal census infrastructure covering the past 170 years of United States history. DCDL is digitizing and creating linkages between nearly a billion records across the 1960 through 1990 U.S. censuses, as well as to already-linked records from the censuses of 1940, 2000, 2010, and 2020. Our main goals in this article are to (1) describe the development of the DCDL and the protocol we will follow to build the linkages between the census files, (2) outline the techniques we will use to evaluate the quality of the links, and (3) show how the assignment and evaluation of these linkages leverages the joint use of routinely collected administrative data and non-routine survey data.